Mohlis Supriandi's Political Strategy in Village Head Election in Pasir Panjang Village, East Mempawah Sub-district, Mempawah Regency - Anwar, Hairil (International Journal of Education, Vocational and Social Science, 2025)
The purpose of the research is to describe the Political Strategy of Mohlis Supriandi in the Election of Pasir Panjang Village Head, East Mempawah District, Mempawah Regency. Descriptive research type, with a qualitative approach (method). Informants were determined by purposive technique, namely: Elected Village Head, success team, religious leaders, community leaders, and voters. Data collection using interview techniques and documentation techniques. The results illustrate an offensive market expansion strategy in the form of offering new programs, modifying old programs into new forms that are more attractive and more profitable delivered through open campaigns and through a big family approach influential as an effective strategy to attract voters, in addition to the candidate's figure factor, and the candidate's qualified political communication skills. The defeat factor of the incumbent candidate (Suhardi) was due to public distrust in the leadership of 2 (two) periods or 12 years in office, lack of transparency in budget use, uneven development and social assistance, and lack of community involvement in every development program proposal. Market penetration strategy through increasing the potential of the target group by recruiting opposing teams, and using shadow communication channels outside the team. The defense strategy is done by clarifying the issues that come with examples and simple language that is easy to understand.